Serine proteases as luminal mediators of intestinal barrier dysfunction and symptom severity in irritable bowel syndrome - Edogawa, Shoko (Gut, 2019)
OBJECTIVE: The intestinal lumen contains several proteases. Our aim was to determine the role of fecal proteases in mediating barrier dysfunction and symptoms in IBS. DESIGN: 39 IBS patients and 25 healthy volunteers completed questionnaires, assessments of in vivo permeability, ex vivo colonic barrier function in Ussing chambers, tight junction (TJ) proteins, ultrastructural morphology, and 16s sequencing of fecal microbiota rRNA. A casein-based assay was used to measure proteolytic activity (PA) in fecal supernatants (FSNs). Colonic barrier function was determined in mice (ex-germ free) humanized with microbial communities associated with different human PA states. RESULTS: IBS patients had higher fecal PA than healthy volunteers. 8/20 post infection-IBS (PI-IBS) and 3/19 IBS-C had high PA (>95 percentile). High PA patients had more and looser bowel movements, greater symptom severity, higher in vivo and ex vivo colonic permeability. High PA FSNs increased paracellular permeability, decreased occludin and increased pMLC expression. Serine but not cysteine protease inhibitor significantly blocked high PA FSN effects on barrier. The effects on barrier were diminished by pharmacological or siRNA inhibition of PAR-2. High PA IBS patients had lower occludin expression, wider TJs on biopsies and reduced microbial diversity than low PA patients. Mice humanized with high PA IBS microbiota had greater in vivo permeability than those with low PA microbiota. CONCLUSION: A subset of IBS patients, especially in PI-IBS, has substantially high fecal PA, greater symptoms, impaired barrier and reduced microbial diversity. Commensal microbiota affects luminal proteolytic activity which can influence host barrier function.